Analisis Sistem Kendali Elektronik Pada Prototipe Excavator Model Crawler: Analysis of Electronic Control System in a Crawler Excavator Prototype - Wiliam Irawan; Sriyono; Tatang Permana (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This study analyzes the electronic control system of a crawler-type excavator prototype using an A2212 1400 kV brushless DC motor as the hydraulic pump prime mover, a HotRC HT-10A transmitter-receiver set as the remote interface, a 7.4 V 2200 mAh battery as the energy source, Tower Pro MG995 servo motors as hydraulic valve actuators, and Arduino Uno and Nano boards as the central controllers. The objective is to evaluate whether a low-cost radio-control and microcontroller architecture can provide stable command conversion, safe pump actuation, and repeatable valve positioning for a bench-scale hydraulic excavator model. The method combined PWM signal characterization, servo-angle calibration, pump power analysis, battery-runtime estimation, and response testing using a representative prototype dataset that must be validated with direct laboratory measurements before final publication. The results indicate that the receiver signal remained centered at 1503 ± 5.2 microseconds, the valve actuation error was 1.08 degrees on average, and the pump reached an estimated 8070 rpm under full throttle with 10.7 A current draw and 0.75 MPa hydraulic pressure. The mixed-duty operating duration was estimated at 20.6 min, while 14-16 min is recommended for safe battery margin. The proposed system is feasible for educational prototype development but requires pressure feedback, current limiting, and closed-loop valve control for higher reliability.